Entrepreneurship Assistance to SMEs and Batik Centers National PKM Activities in Giriloyo Batik Village, in the Special Region of Yogyakarta, Indonesia - Meitiana; Roby Sambung; Vivy Kristinae (PT FORMOSA CENDEKIA GLOBAL, 2023)
The importance of Entrepreneurship Assistance activities in Small and Medium Industries (IKM) and Batik Centers in National Community Service Activities (PKM) in Giriloyo Batik Village, Yogyakarta Special Region, Indonesia. The Batik industry in Indonesia has a rich history and an important role in the country's culture and economy. Entrepreneurship mentoring is a concept that offers guidance, training and support to entrepreneurs to develop their business. This report details mentoring methods, the positive impacts that have been seen, and the resulting benefits, including increased product quality, income, job creation, and development of local cultural identity. References from the literature help provide a solid foundation in understanding the concepts underlying these activities and their impact on local communities and creative industries. In conclusion, entrepreneurial assistance activities in Giriloyo Batik Village are an important step in supporting the growth of the batik industry and the welfare of the local community, and can be an inspiration for similar communities throughout Indonesia.